2017
DOI: 10.1136/gutjnl-2016-313128
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate modelling of faecal bacterial profiles of patients with IBS predicts responsiveness to a diet low in FODMAPs

Abstract: NCT02107625.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
179
5
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(199 citation statements)
references
References 36 publications
7
179
5
8
Order By: Relevance
“…71 However, long term use of such an intervention can decrease microbial short chain fatty acid production which in turn may have negative implications for human health. A recent study identified microbiome markers which predict a positive response to FODMAP 72 with the potential to allow optimization of therapy and minimizing undesirable adverse effects in individuals less likely to respond. An important aspect of the gut microbiome is its role in determining host responses to dietary components given that the microbiome plays an important role in metabolism of dietary nutrients.…”
Section: Targeting the Microbiome To Improve Healthmentioning
confidence: 99%
“…71 However, long term use of such an intervention can decrease microbial short chain fatty acid production which in turn may have negative implications for human health. A recent study identified microbiome markers which predict a positive response to FODMAP 72 with the potential to allow optimization of therapy and minimizing undesirable adverse effects in individuals less likely to respond. An important aspect of the gut microbiome is its role in determining host responses to dietary components given that the microbiome plays an important role in metabolism of dietary nutrients.…”
Section: Targeting the Microbiome To Improve Healthmentioning
confidence: 99%
“…I ein ny studie er samanhengen mellom fekal bakterieprofil og respons på diettbehandling ved irritabel tarm-syndrom undersøkt (1). Studien byggjer på sekundaeranalysar av 61 pasientar frå ein intervensjonsstudie.…”
Section: Illustrasjonsfoto: Chrischrisw/istockunclassified
“…Patients with IBS following a low FODMAP diet had significant decreases from baseline in the quantity of fecal bacteria (i.e. Mycoplasma hominis, Bifidobacterium, Actinobacteria) after 4 weeks [51]. However, the implications of a long-term low FODMAP diet on the gut microbiota in IBS are currently unknown [50].…”
Section: Low Fodmap Dietmentioning
confidence: 99%